A Comprehensive Literature Review of Olfactory Impairment and Frailty - Angelica, Angelica; Laurensia, Laurensia; Kemala Putri, Kemala Putri (The International Journal of Medical Science and Health Research, 2024)
Background: The literature on olfactory impairment and its connection to frailty reveals significant insights into how sensory decline impacts various aspects of health and well-being in older adults. The foundational work by (Wongrakpanich et al., 2016) establishes the prevalence of olfactory dysfunction and its predictive value for cognitive decline and mortality. This is further supported by (S. Fluitman et al., 2019), who elucidate the relationship between olfactory impairment and nutritional health, highlighting how diminished olfactory function can lead to appetite suppression and subsequent undernutrition, thereby contributing to frailty. Literature Review: The exploration of age-related olfactory decline by (Kondo et al., 2020) emphasizes the multifactorial nature of this sensory loss, identifying lifestyle factors such as smoking and sinonasal diseases that exacerbate olfactory dysfunction. Moreover, (Tzeng et al., 2021) draw parallels between olfactory impairment and neurodegenerative diseases, suggesting that olfactory dysfunction may serve as a critical early indicator of cognitive decline, particularly in Alzheimer's disease.The research by (Iritani et al., 2021) and (Park et al., 2021) extends this discourse by linking olfactory deficits to geriatric syndromes, reinforcing the notion that sensory health is intertwined with cognitive function and overall frailty. Conclusion: In conclusion, the body of literature presents a compelling case for the significance of olfactory health in the context of frailty among older adults. The multifaceted relationships between olfactory impairment, cognitive decline, nutritional health, physical strength, and social interactions highlight the need for comprehensive approaches to assess and address sensory health in geriatric care. Interventions aimed at improving olfactory function could play a pivotal role in enhancing the quality of life and mitigating the adverse effects of frailty in this vulnerable population.